Case report of belt electrode-skeletal muscle electrical stimulation for acute heart failure with severe obesity: a novel therapeutic option for acute phase rehabilitation - Mochizuki, Yuto; Jimba, Takahiro; Yasukawa, Syota; Katsura, Aritomo; Fukuda, Akira; Ando, Jiro (Frontiers in Cardiovascular Medicine, 2024)
Background Belt electrode skeletal muscle electrical stimulation (B-SES) is an emerging therapy anticipated to yield more favorable outcomes than conventional neuromuscular electrical stimulation (NMES), owing to its larger stimulation area. However, information on its efficacy and safety in patients with heart failure remains limited. Case presentation A 43-year-old man with a body mass index of 41 kg/m2 was admitted to our hospital for acute heart failure due to dilated cardiomyopathy. The patient required prolonged catecholamine support owing to poor cardiac function, and heart transplantation was considered. We initiated a mobilization program, but the patient's mobility was highly limited due to severe obesity and symptomatic orthostatic hypotension. B-SES was introduced to accomplish weight loss and early ambulation. We applied an intensive monitoring program for safe use and modulated the intensity of B-SES according to physical function. During the B-SES program, the patient's body weight decreased from 89.6 kg to 78.6 kg. Sequential evaluations of body composition and skeletal muscle ultrasonography revealed improved muscle mass, quality, and physical function. Furthermore, we explored the workload of B-SES using expiratory gas analysis. No adverse events were observed during B-SES. Discussion We successfully used B-SES to improve muscle function and morbidity in the treatment of acute heart failure. B-SES could be an option for patients with heart failure who have limited mobility and obesity.